Solution of fifth order boundary value problems by using local polynomial regression - Çağlar, Hikmet; Çağlar, Nazan (ELSEVIER SCIENCE INC, 360 PARK AVE SOUTH, NEW YORK, NY 10010-1710 USA, 2007)
In this paper, we present a novel method based on the local polynomial regression for solving of fifth order boundary value problems. The method is tested on numerical example to demonstrate its usefulness. The method presented in this paper is also compared with those developed by Siddiqi and Akram [Solution of fifth order boundary value problems using nonpolynomial spline technique, Appl. Math. Comput. 175 (2006) 1575-1581], as well and is observed to be better. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: boundary value problems; local polynomial regression; kernel functions; sınır değer problemleri; yerel polinom regresyon; çekirdek fonksiyonları